Penguatan Karakter Peduli Lingkungan melalui Pendidikan Agama Islam di Madrasah Tsanawiyah Kota Samarinda - Fitri Ramadani; Eka Mahmud; Sri Susmiyati (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2025)
Environmental degradation calls for character education that is not merely normative but genuinely transformative. Islamic Religious Education (Pendidikan Agama Islam/PAI) holds strategic potential in fostering ecological awareness grounded in faith-based values. This study aims to analyze the process of internalizing environmental care character through PAI and to identify its supporting and inhibiting factors in Islamic junior secondary schools (Madrasah Tsanawiyah) in Samarinda. This research employed a qualitative approach with a multisite case study design conducted at MTs Al Mujahidin and MTs Al Azhar Samarinda. Data were collected through observation, in-depth interviews, and documentation involving 12 informants, including principals, vice principals for curriculum, PAI teachers, and students. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, with credibility ensured through source and technique triangulation. The findings reveal that strengthening environmental care character occurs through three systematic stages: inculcation (integration of ecological values into PAI instruction), habituation (moral reinforcement and teacher role modeling), and institutionalization (embedding practices into school culture). Supporting factors include adequate infrastructure, consistent monitoring, and teachers’ professionalism, while challenges involve varying levels of student awareness, peer influence, and institutional practices that generate waste. Theoretically, this study proposes a Three-Stage Religious-Ecological Internalization Model as a conceptual contribution to faith-based character education theory. The model demonstrates that PAI functions not only as a normative framework but also as an operational mechanism for shaping ecological behavior through the integration of theological, pedagogical, and social-practical dimensions.